2009
DOI: 10.1377/hlthaff.28.2.w282
|View full text |Cite
|
Sign up to set email alerts
|

Costs And Benefits Of Health Information Technology: New Trends From The Literature

Abstract: ABSTRACT:To understand what is new in health information technology (IT), we updated a systematic review of health IT with studies published during [2004][2005][2006][2007]. From 4,683 titles, 179 met inclusion criteria. We identified a proliferation of patient-focused applications although little formal evaluation in this area; more descriptions of commercial electronic health records (EHRs) and health IT systems designed to run independently from EHRs; and proportionately fewer relevant studies from the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
195
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(214 citation statements)
references
References 9 publications
9
195
0
10
Order By: Relevance
“…5,6,20,21 This study supports prior work demonstrating the capacity of health information technology to improve processes of care and of CCDS to change provider behavior. [22][23][24] Our study found a median benefit of 2.1 % to clinical process-of-care measures, similar to the rate of 3.8 % found in a 2009 Cochrane Review on the effect of CCDS on process of care. In the same Cochrane Review, only 4 of the 32 included studies looked at CCDS tools as a way to reduce unwanted behavior.…”
Section: Discussionsupporting
confidence: 84%
“…5,6,20,21 This study supports prior work demonstrating the capacity of health information technology to improve processes of care and of CCDS to change provider behavior. [22][23][24] Our study found a median benefit of 2.1 % to clinical process-of-care measures, similar to the rate of 3.8 % found in a 2009 Cochrane Review on the effect of CCDS on process of care. In the same Cochrane Review, only 4 of the 32 included studies looked at CCDS tools as a way to reduce unwanted behavior.…”
Section: Discussionsupporting
confidence: 84%
“…5 There is a large body of literature on the experiences of specific organizations and providers in implementing electronic health records (EHRs) and other related applications such as e-prescribing and computerized physician order entry systems. [6][7][8][9] ICTs can also enable new ways of delivering care. For example, telehealth can provide access to advanced services that would not otherwise be available in rural and remote areas.…”
Section: Background and Significancementioning
confidence: 99%
“…The good news is that Vietnam has the potential to develop a functioning electronic health records (EHR) system in the future as the system is centralized and professionals show good awareness of EHR's roles and values in delivering better e-health services to patients (Detmer, 2003;Goldzweig, Towfigh, Maglione, & Shekelle, 2009;Hochwarter, Chuc, & Larsson, 2014) and improving doctor-patient relationships (Tang & Lansky, 2005).…”
Section: A Brief Literature Reviewmentioning
confidence: 99%